FAKTOR-FAKTOR YANG MEMENGARUHI KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN (Studi Kasus Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia tahun 2014-2017) - Diah Suci Wulandari, 15.05.52.0180; Srimindarti,, Ceacilia (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of liquidity, leverage, profitability, firm size, company age and public share ownership on the completeness of financial statement disclosures. The population of this research is mining companies listed on the Indonesia Stock Exchange. The sampling method used purposive sampling with the 2014 to 2017 research period and obtained as many as 130 companies. The results of this study indicate that the liquidity variable has a positive and insignificant effect on the completeness of financial statement disclosures. leverage variable negatively has no significant effect on the completeness of financial statement disclosures. profitability variables have a positive and insignificant effect on the completeness of financial statement disclosures. company size variables have a significant positive effect on the completeness of financial statement disclosures. company age variables and public share ownership variables have a significant negative effect on the completeness of financial statement disclosures.